A Review of Field Experiments on the Effect of Forest Bathing on Anxiety and Heart Rate Variability - Marc R Farrow PT; Kyle Washburn RN, BSN, CEN (SAGE Publishing, 2019)
Many studies have explored the physiological and psychological benefits of the Japanese nature therapy practice of "shinrin-yoku," known in the West as forest bathing. This review article has narrowed its focus to include the most recent literature about the beneficial effects of forest bathing on heart rate variability, expressed as an increase in InHF, indicating activation of the parasympathetic nervous system and also its effect on reducing anxiety.